PENGARUH KUALITAS LAYANAN DAN CITRA PERUSAHAAN TERHADAP KEPUASAN DAN LOYALITAS NASABAH PADA PT ASURANSI ALLIANZ LIFE INDONESIA - Tsamara Fara Safira; Siti Rahayu; Fitri Novika Widjaja (MANAJEMEN DEWANTARA, 2026)
This study aims to analyze the influence of service quality and corporate image on customer satisfaction and customer loyalty at PT Asuransi Allianz Life Indonesia. The Indonesian life insurance industry faces low penetration and a high lapse ratio despite its large market potential. Using a quantitative approach and PLS-SEM, data were collected from 154 Allianz customers across Indonesia through purposive sampling. The results of this study indicate that the factors of Service Quality and Corporate Image have a significant influence on Customer Loyalty through Customer Satisfaction. In this relationship, Customer Satisfaction has a positive and significant effect on Customer Loyalty, and achieving customer satisfaction requires a strong Corporate Image and high-quality Service Quality. Among these two factors, the most dominant influence is Service Quality, followed by Corporate Image.